Crecimiento, estado fitosanitario y mortalidad de la plantación N° 11 de Carapa guianensis "andiroba", CIEFOR - Puerto Almendra, Loreto - Perú. 2022 - Villar del Aguila, Enzo Vinicio (2023)
The study was carried out in the Carapa guianensis plantation with the objective of determining the increase in diameter, height growth quality and survival. The increase in diameter, height growth are dissimilar between the strips under study. There is no statistical difference between the average increase in diameter and height and the evaluation strips. The strips presented a survival of 58%, while the mortality of the plants reached 42%. The largest number of seedlings has GOOD quality (60 seedlings) which represents 51.7% of the total, followed by REGULAR quality with 46 living individuals which represents 39.7% and, finally, the fewest individuals were observed in the BAD quality with 10 seedlings that represented 8.6% of the total. It is recommended to carry out similar studies with other native forest species in CIEFOR - Puerto Almendra.